Relationship between sleep duration and TV time with cardiometabolic risk in adolescents - Ana Paula Sehn; Anelise Reis Gaya; Arieli Fernandes Dias; Caroline Brand; Jorge Mota; Karin Allor Pfeiffer; Javier Brazo Sayavera; Jane Dagmar Pollo Renner; Cézane Priscila Reuter (Komiyama Printing Co. Ltd, 2020)
Abstract Objective To verify the association between sleep duration and television time with cardiometabolic risk and the moderating role of age, gender, and skin color/ethnicity in this relationship among adolescents. Methods Cross-sectional study with 1411 adolescents (800 girls) aged 10 to 17 years. Television time, sleep duration, age, gender, and skin color/ethnicity were obtained by self-reported questionnaire. Cardiometabolic risk was evaluated using the continuous metabolic risk score, by the sum of the standard z-score values for each risk factor: high-density lipoprotein cholesterol, triglycerides, glycemia, cardiorespiratory fitness, systolic blood pressure, and waist circumference. Generalized linear regression models were used. Results There was an association between television time and cardiometabolic risk (β, 0.002; 95% CI, 0.001; 0.003). Short sleep duration (β, 0.422; 95% CI, 0.012; 0.833) was positively associated with cardiometabolic risk. Additionally, age moderated the relationship between television time and cardiometabolic risk (β, − 0.009; 95% CI, − 0.002; − 0.001), suggesting that this relationship was stronger at ages 11 and 13 years (β, 0.004; 95% CI, 0.001; 0.006) compared to 13 to 15 years (β, 0.002; 95% CI, 0.001; 0.004). No association was found in older adolescents (β, 0.001; 95% CI, − 0.002; 0.002). Conclusions Television time and sleep duration are associated with cardiometabolic risk; adolescents with short sleep have higher cardiometabolic risk. In addition, age plays a moderating role in the relationship between TV time and cardiometabolic risk, indicating that in younger adolescents the relationship is stronger compared to older ones.